الفاتورة الالكترونية كآلية لتقليص منافذ الاقتصاد الموازي في بيئة الأعمال الجزائرية - حجيرة بدرالدين; فالي نبيلة; عجلان عياشي (جامعة الوادي University of Eloued, 2024)
يعاني الاقتصاد الجزائري من صعوبات تعيق نموه وتطوره، منها المرتبطة بالاقتصاد الموازي، الذي تسعى الدولة إلى تأطيره ضمن الدورة الاقتصادية الرسمية، من خلال اتباع سياسات متعددة واستخدام آليات مختلفة. هذه الدراسة تناولت الفاتورة الالكترونية كآلية لإدراج الاقتصاد الموازي ضمن الدورة الرسمية لتقليص منافذه وكبح آثاره، بالاستفادة من تجارب دولية ضمن التحول العالمي نحو الاقتصاد الرقمي. وتوصلت إلى اعتبارها من الحلول الهامة لمعالجة معضلة الاقتصاد الموازي في بيئة الأعمال الجزائرية. The Algerian economy suffers from difficulties hindering its growth and development. Related to the informal economy, that the State seeks to frame it in the formal economic cycle, following several policies and using different mechanisms. This study treated the electronic invoice as a mechanism to include the informal economy in the official business cycle to reduce its effects, building on international experiences in transition to a digital economy. The study found that electronic invoice is one of the important solutions to the problem of the informal economy in the Algerian business environment
Electronic invoice as a mechanism to reduce the informal economy accesses. in the Algerian business environment
Keywords: Electronic invoice; Informal economy; Tax evasion